1995
DOI: 10.1103/physreve.52.4632
|View full text |Cite
|
Sign up to set email alerts
|

Scaling in late stage spinodal decomposition with quenched disorder

Abstract: We study the late stages of spinodal decomposition in a Ginzburg-Landau mean field model with quenched disorder. Random spatial dependence in the coupling constants is introduced to model the quenched disorder. The effect of the disorder on the scaling of the structure factor and on the domain growth is investigated in both the zero temperature limit and at finite temperature. In particular, we find that at zero temperature the domain size, R(t), scales with the amplitude, A, of the quenched disorder as R(t) =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
23
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
(56 reference statements)
11
23
0
Order By: Relevance
“…(The final point, corresponding to a total reduced surfactant density of 0.09, lies below this line probably because the simulation had not fully equilibrated.) It is worth noting that the result shown in Fig. 14 is also consistent with the relationship found between the final domain size and the amplitude of disorder in systems with quenched impurities, as determined by Gyure et al 20 . 15, which is a plot of domain size versus ln t for the case of surfactant density 0.14, indicates that in this case the slow domain growth may go as (ln t) θ with θ ≃ 0.5 over the dominant timescale of the simulations (beyond the initial transient region) and before the domain size saturates completely.…”
Section: Figsupporting
confidence: 89%
See 2 more Smart Citations
“…(The final point, corresponding to a total reduced surfactant density of 0.09, lies below this line probably because the simulation had not fully equilibrated.) It is worth noting that the result shown in Fig. 14 is also consistent with the relationship found between the final domain size and the amplitude of disorder in systems with quenched impurities, as determined by Gyure et al 20 . 15, which is a plot of domain size versus ln t for the case of surfactant density 0.14, indicates that in this case the slow domain growth may go as (ln t) θ with θ ≃ 0.5 over the dominant timescale of the simulations (beyond the initial transient region) and before the domain size saturates completely.…”
Section: Figsupporting
confidence: 89%
“…9) so that we are able to observe any algebraic exponent for the ln t growth. If the slow growth in these systems can indeed be related in some way to that in systems with quenched impurities 20 , then we would expect to find some power θ for the growth function (ln t) θ , which decreases as the amount of surfactant in the system is further increased. In this initial case we find a value θ ≃ 3.0 for the timescale of the simulation beyond the very early-time transient behavior.…”
Section: Figmentioning
confidence: 95%
See 1 more Smart Citation
“…(1) is reported in some experiments [16,17], the asymptotic growth-law R(t) is much slower than in a clean system [16][17][18][19][20]. Similar conclusions are reached in the numerical studies of models of disordered ferromagnets, such as the kinetic Ising model in the presence of random external fields [21][22][23][24][25][26][27][28][29][30][31][32], with varying coupling constants [32][33][34][35][36][37][38][39], or in the presence of dilution [33,38,[40][41][42][43][44][45][46][47]49]. A natural question is, then, whether the percolation effects observed in bi-dimensional clean systems show up also in the disordered ones.…”
Section: Introductionsupporting
confidence: 79%
“…8 this form fits our results extremely well across the full time scale of the simulations and for all surfactant concentrations considered. We also investigated a fit of the logarithmic form R(t) = a + b(ln t) c , which describes the phase-separation of binary alloys in the presence of impurities [37]. Obviously, this form is unable to describe the late time saturation of the domain size and we found that the root-mean-square errors using this form to describe the early times of domain formation are also an order of magnitude larger than that of the stretched exponential form.…”
Section: The Effect Of Surfactant On Domain Growth Dynamicsmentioning
confidence: 99%